STUDENTS’ SELF-CONFIDENCE IN SPEAKING FOR A LIVE PRESENTATION: A LITERATURE REVIEW - Amhar Amin Lar, Maulidya; Maulina, Maulina (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
The ability to speak English is a challenge for students in Indonesia as users of English as a foreign language. This study aims to determine whether there is a relationship between students' confidence in their ability to speak English using a live presentation method. The researchers used the Prisma 2009 statement to spell out the process. Ten articles were presented to collect the data related to students' self-confidence and speaking skills. This paper finds that student self-confidence is an essential component that determines the mastery of speaking skills.